(untitled) (Anclajes, 2026)
Eight decades after its end, the Spanish Civil War continues to be a recurring setting in contemporary Spanish fiction, providing context for a wide variety of narratives. In recent years, however, a group of young writers has emerged who have opted for certain thematic and formal particularities in their texts on the conflict, giving rise to new approaches to the narrative and reconstruction of recent memory in the country. The novels of these writers address personal, family, or collective memory in a unique way, with the aim of problematising it, and among other common features, the presence of the ghostly in their works is striking. Although this research analyses different literary works related to the Civil War, it focuses in depth on Paisaje nacional (2024) by Millanes Rivas, as it allows for a paradigmatic study of these novel and original narrative approaches.